2011
DOI: 10.1214/ecp.v16-1625
|View full text |Cite
|
Sign up to set email alerts
|

On a species survival model

Abstract: In this paper we provide some sharp asymptotic results for a stochastic model of species survival recently proposed by Guiol, Marchado, and Schinazi.1 Introduction and statement of results Recently, Guiol, Marchado, and Schinazi [7] proposed a new mathematical framework for modeling species survival which is closely related to the discrete Bak-Sneppen evolution model. In the original Bak-Sneppen model [3] a finite number of species are arranged in a circle, each species being characterized by its location and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 12 publications
0
12
0
2
Order By: Relevance
“…Observe that from Ben Ari et al[2] it would be also possible to get a Central Limit Theorem and a Law of the Iterate logarithm for R t .3Construction of the process. The construction uses ideas from Harris Graphical method for Markov Processes and basically take advantage from projections properties of a bi-dimensional Poisson process with rate 1.…”
mentioning
confidence: 99%
“…Observe that from Ben Ari et al[2] it would be also possible to get a Central Limit Theorem and a Law of the Iterate logarithm for R t .3Construction of the process. The construction uses ideas from Harris Graphical method for Markov Processes and basically take advantage from projections properties of a bi-dimensional Poisson process with rate 1.…”
mentioning
confidence: 99%
“…We note that for the GMS model and its generalizations, with µ ∼ U([0, 1]) (where U(I) is the uniform distribution on I), the fraction of surviving species in any I ⊆ [f c , 1] is proportional to µ(I). This is still true in our case when I ⊆ (f c , 1], but it does not hold for 1])/n → 0 (the exact rate of convergence for the GMS is studied in [3]), while again this needs not to be true if f c is an atom for µ. In this example we choose µ := αδ 1/2 + (1 − α)ν (where ν ∼ U([0, 1])); the case α = 0 is discussed in [6].…”
Section: 1mentioning
confidence: 84%
“…Observe that in Theorem 2.2 we used Z n as a normalizing factor for Z n (A) but there are two other natural choices: n (to compare with [2,9]) and N n (to compare with [3,6]).…”
Section: 1mentioning
confidence: 99%
See 1 more Smart Citation
“…It is shown that this model obeys power law behavior for avalanche duration and size, behavior observed in numerical simulations for the original Bak-Sneppen model. Another variant of the Bak-Sneppen model was introduced in [9], studied in [5], and generalized in [14]. Here the number of species follows a path of reflected random walk transient to infinity.…”
Section: Introductionmentioning
confidence: 99%